Analyzing the health benefits of biofortified staple crops by means of the disability-adjusted life years approach: a handbook focusing on iron, zinc and vitamin A - Stein, Alexander J.; Meenakshi, Jonnalagadda V.; Qaim, Matin; Nestel, Penelope; Sachdev, H.P.S.; Bhutta, Zulfiqar A. (International Food Policy Research Institute, 2005)
Biofortified staple crops – food crops bred for higher micronutrient content – are expected to reduce micronutrient deficiency and its accompanying adverse health outcomes. Health benefits can be measured and expressed in terms of the number of “disability-adjusted life years” (DALYs) saved due to the intervention. This quantification of health benefits can be used in cost-effectiveness and in cost-benefit analyses, by attributing a monetary value to DALYs and juxtaposing this benefit and the research and development costs of the biofortified crop. This handbook describes how to conduct these impact analyses for staple crops biofortified with iron, zinc or beta-carotene. It outlines the underlying method, explains the individual steps of the analysis, and details information and data requirements. The results of analyses of the type described here should prove useful for demonstrating the economic feasibility of biofortification, estimating its impact, creating awareness of this new intervention, directing research priorities, and identifying constraints early on.